2010
DOI: 10.1007/s00436-010-1740-2
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal activity and acute toxicity assessment of triterpene acids

Abstract: The present study evaluates the in vitro and in vivo trypanocidal activity of ursolic acid and oleanolic acid against the Bolivia strain of Trypanosoma cruzi. Their acute toxicity is also assessed on the basis of median lethal dose (DL50) determination and quantification of biochemical parameters. Ursolic acid is the most active compound in vitro, furnishing IC50 of 25.5 microM and displaying 77% of trypomastigote lysis at a concentration of 128 microM. In agreement with in vitro assays, the results obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 23 publications
1
10
1
1
Order By: Relevance
“…UA is generally considered to be safe and have minimal adverse effect. Neither mortality nor any signs of toxicity with orally administrating a single dose as high as 2,000 mg/Kg was observed in acute toxicity study in mice [29]. In our study, no toxic effect on experimental animals was observed in our administrating dose of UA (about 200 mg/Kg body weight day in H-UA group).…”
Section: Discussioncontrasting
confidence: 65%
“…UA is generally considered to be safe and have minimal adverse effect. Neither mortality nor any signs of toxicity with orally administrating a single dose as high as 2,000 mg/Kg was observed in acute toxicity study in mice [29]. In our study, no toxic effect on experimental animals was observed in our administrating dose of UA (about 200 mg/Kg body weight day in H-UA group).…”
Section: Discussioncontrasting
confidence: 65%
“…La saponina denominada ácido 3-O-β-D-glucopiranosil oleanólico aislada de las semillas de Randia dumetornm Lam. [75], y de otras plantas [76][77][78], ha mostrado una importante actividad antiinflamatoria en las fases exudativa y de proliferación de la inflamación con dosis entre 25 y 100 mg/kg. Puesto que este mismo tipo de saponina ha sido previamente identificado en las semillas de quinua (véase tabla 1), se podría esperar la manifestación de esta misma actividad por la fracción de saponinas de quinua.…”
Section: Actividad Antiinflamatoriaunclassified
“…In addition, other triterpenoid molecules structurally related to MA display very different cytotoxic and antiparasitic activities. Thus, cucurbitane-type triterpenoids have been recently shown to display anti-malarial activity [27], while ursane-type urosolic acid was reported to inhibit growth of Trypanosoma cruzi [28] showing in contrast low anti-plasmodial activity [29]. However, hybrid molecules consisting on ursolic acid bound to pharmacophores showed enhanced inhibitory activity on Plasmodium, presumably by facilitating the access of the bound pharmacophore to haem [30].…”
Section: Introductionmentioning
confidence: 99%